GEN_MAT: A MATLAB‐based map generalization algorithm toolbox. Issue 6 (13th August 2017) - Wang, Yiheng; Tian, Jing; Yu, Mengting; Ren, Chang; Wu, Xiaohuan
Abstract: Assistive tools are important for improving teaching and learning quality in courses that involve practical work. This article presents an overview of GEN_MAT, the first MATLAB‐based map generalization algorithm toolbox. The toolbox provides 42 map generalization algorithms for aggregation, selective omission, simplification, smoothing, collapse, agglomeration, merging, dissolving, displacement, and typification. A beta test of the application of GEN_MAT in teaching and learning was conducted. Evaluations showed that GEN_MAT has positive effects on teaching and learning. Comparing tool‐based and non‐tool‐based courses indicated that the experimental group performed better than the control group, and the two groups exhibited significant discrepancy ( p < 0.05) in confidence, awareness, skills and attitudes or behaviors.